GE_GERICHTE C/24701/2016 vom 26. September 2018 - GE Cour de justice (2018)
PROTECTION DE L'UNION CONJUGALE ; DOMICILE COMMUN ; DROIT DE GARDE ; OBLIGATION D'ENTRETIEN ; ENFANT ; CONJOINT ; DROIT D'ÊTRE ENTENDU ; REVENU HYPOTHÉTIQUE | Cst.29; CPC.314.al2; CC.163; CC.176.al1.ch2; CC.176.al3; CPC.317.al2